PAPAN HURUF FLANEL: MEDIA PEMBELAJARAN KEAKSARAN AWAL UNTUK ANAK USIA DINI - Jazariyah Jazariyah (AWLADY : Jurnal Pendidikan Anak, 2019)
Attractive learning media become an attraction in early childhood learning. The use of media can provides convenience for teachers of Early childhood education (PAUD) in delivering material to be given to children. This study aims to conduct development research in making learning media. The media developed is alphabet flannel board (letter board). This media development was carried out for the introduction of early literacy, using the Research and Development (R & D) research model. The stages of R & D research include potential problems, information gathering, product design, design validation, design revisions, products, small-scale product trials, large-scale trials and mass production. In this study not all stages are carried out considering the limited time and cost so that the research only reaches the stage of feasibility validation and design revision to be the final product. Feasibility of the Alphabet Flannel Board is validated by the expert and the assessment of the user in this case PAUD teacher. Based on data analysis, the results of this study indicate that the Alphabet Flannel Board is quite feasible to be used as media. The mean value of the validation shows 3.25 of a scale of 5 which means it's quite decent.